Essential commodities prices, availability, and market actors’ perceptions: June 2025 - Siddig, Khalid; Rakhy, Tarig; Nigus, Halefom Yigzaw; Mohamed, Shima; Abushama, Hala (International Food Policy Research Institute, 2025)
This report analyzes key market trends in Sudan from February to June 2025, focusing on the prices, availability, and quality of essential commodities—cereals, vegetables, animal products, agricultural inputs, fuel, and exchange rates. Consistent with previous editions, it reveals significant spatial and temporal disparities across Sudan’s 18 states.